PENGGUNAAN TERUNG RIMBANG PADA MATERI IKATAN KIMIA DAN BENTUK MOLEKUL UNTUK MENINGKATKAN PEMAHAMAN PESERTA DIDIK - Khairiah Khairiah (UIN AR-RANIRY, 2019)
Study on the use of molymod from turkey berries to improve students' understanding of chemical bonding material and molecular shape has been carried out. This study aimed to improve student learning outcomes and activities in studying chemical bonding and molecular shapes. This study was a classroom action research conducted in three cycles. The subjects of this study were students of class XI IA 2 of SMAN 1 Sukamakmur, Aceh Besar. The increasing of student learning outcomes of the three cycles in a row that was 51.19, 61.90, and 75. The classical completeness obtained in each cycle was 19%, 57%, and 86% with the completeness criteria of low, medium, and high graduation. Besides looking at the learning outcomes, the activity of students has also seen an increase in each cycle. The activities of the student in each cycle respectively were obtained about 43%, 62%, and 81% with the criteria of quite active, active, and very active. Based on the result of the learning outcomes and observation of students showed that the learning of chemical bonds and molecular models by using turkey berries has been successfully conducted.